Situational judgment tests as measures of 21st century skills: Evidence across Europe and Latin America - HERDE, Christoph (Institutional Knowledge at Singapore Management University, 2019)
Over the years, various governmental, employment, and academic organizations have identified a list of skills to successfully master the challenges of the 21st century. So far, an adequate assessment of these skills across countries has remained challenging. Limitations inherent in the use of self-reports (e.g., lack of self-insight, socially desirable responding, response style bias, reference group bias, etc.) have spurred on the search for methods that could complement or even substitute self-report inventories. Situational judgment tests (SJTs) have been proposed as one of the complements/alternatives to the traditional self-report inventories. SJTs are low-fidelity simulations that confront participants with multiple domain-relevant situations and request to choose from a set of predefined responses. Our objectives are twofold: (a) outlining how a combined emic-etic approach can be used for developing SJT items that can be used across geographical regions and (b) investigating whether SJT scores can be compared across regions. Our data come from Laureate International Universities (N = 5,790) and comprise test-takers from Europe and Latin America who completed five different SJTs that were developed in line with a combined emic-etic approach. Results showed evidence for metric measurement invariance across participants from Europe and Latin America for all five SJTs. Implications for the use of SJTs as measures of 21st century skills are discussed.